THE ALUMINUM AIR BATTERY PERFORMANCE BY USING RED BRICK AS THE CATHODE TO TURN ON THE LED LIGHTS ON SHIPBOARD - Ayom Buwono; Shahrin Febrian (Jurnal Sains & Teknologi Fakultas Teknik Universitas Darma Persada, 2020)
Metal battery technology of air into a promising alternative power source and its development is being observed throughout the world, this technology is applied in various fields such as electric cars and even electric boats. Aluminum into the anode material has advantages over other metals, red brick became one alternative cathode materials for battery air-conditioned metal, a mixture of these two materials have been studied in many developed countries as an alternative material manufacture battery cathode. In Indonesia, it will be used since the time of our ancestors in many good purposes pottery, building material until the red brick. Then conducted trials to determine the ability of this material as a cathode air on Aluminum-air battery with 6 Mol Potassium Hydroxide as a solution of electrolytes, voltage values with cell dimensions of Ø25 mm and 10 mm thick produce the highest voltage value of 1.28 volts and a current of 29 mA, battery cells can be applied optimally in the light 1 watt when strung together 27 series battery cells. Series or parallel with the system's expected battery by utilizing residual red brick waste can be used for alternative energy sources lighting. Energy produced has properties Sustainable Environment, does not damage the environment, have the availability of the primary material, and has a good safety compared to other batteries.